2007
DOI: 10.1007/s00360-007-0217-9
|View full text |Cite
|
Sign up to set email alerts
|

High-definition spatiotemporal mapping of contractile activity in the isolated proximal colon of the rabbit

Abstract: Four types of contractile activity were identified and characterised in the isolated triple haustrated proximal colon of the rabbit using high-definition spatiotemporal mapping techniques. Mass peristalses were hexamethonium-sensitive deep circular contractions with associated taenial longitudinal contractile activity that occurred irregularly and propagated rapidly aborad, preceded by a zone of local lumen distension. They were sufficiently sustained for each event to occupy the length of the isolated colonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
114
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(129 citation statements)
references
References 24 publications
12
114
2
Order By: Relevance
“…The deep indentations that delineated the haustra did not change in location during experiments, indicating that these are probably fixed points, probably due to connective tissue structures. This is at variance from Lentle et al who reported that all haustral indentations appear to propagate (28). We are currently unable to explain the difference between our results.…”
Section: Are Haustra Fixed?contrasting
confidence: 56%
See 3 more Smart Citations
“…The deep indentations that delineated the haustra did not change in location during experiments, indicating that these are probably fixed points, probably due to connective tissue structures. This is at variance from Lentle et al who reported that all haustral indentations appear to propagate (28). We are currently unable to explain the difference between our results.…”
Section: Are Haustra Fixed?contrasting
confidence: 56%
“…Such activity is likely to form the characteristic shape of the fecal pellets (16,17,35). The effect of hexamethonium indicates that nicotinic transmission is required for this cyclic motor activity (28). Nicotinic transmission mediates most fast excitatory synaptic transmission in enteric circuits (9) and thus underlies many neurally dependent enteric motor functions.…”
Section: Neurogenic Migrating Motor Complexes In the Proximal Colonmentioning
confidence: 99%
See 2 more Smart Citations
“…colon motility; enteric neurons; spatiotemporal maps; peristalsis COLONIC MOTILITY IS CONTROLLED by complex interactive processes in the gut, involving both nerve cells (neurogenic) and spontaneous muscle activity (myogenic). A number of studies have characterized fundamental mechanisms in the colon of the guinea pig, mouse, and rabbit and have shown that propagating contractions underlying peristalsis, or other propulsive motor patterns, require activity in the enteric nervous system (8,11,13,14,17,25).…”
mentioning
confidence: 99%